Efficacy of Entomopathogenic Nematode, Steinernema abbasi PN-1 against Helicoverpa armigera Hubner - P. Vireesha; R. Pandey; M. Shashikala; N. Mehra; S. Kumar (International Journal of Economic Plants)
The experiment was conducted during May 2022 at College of Agriculture, G. B. Pant University of Agriculture & Technology, U. S. Nagar, Pantnagar, Uttarakhand, India. The Steinernema abbasi PN-1 is a local isolate of entomopathogenic nematode isolated from the soil collected from Uttarakhand, India. Under the present study, virulenceof Steinernema abbasi PN-1 against different stages of Helicoverpa armigera Hubner were tested. Virulence studies of S. abbasi PN-1 against H. armigera proved that all larval stages and pupae of H. armigera were found susceptible to the IJs of S. abbasi PN-1. There was a positive correlation between insect mortality and the nematode concentration. The S. abbasi PN-1 caused 100% larval mortality at 48–60 h of post treatment in all tested doses in laboratory. Among the larval instars, 4th instar larvae of H. armigera were more susceptible with a median lethal concentration (LC50) value of 24.37 IJs larva-1 and the median lethal time (LT50) values of 25.63 hours. The 2nd instar larvae was least susceptible with an LC50 value of 78.96 IJs larva-1 and LT50 values of 41.33 hours. The pupal stage was less susceptible than the larval stage with the LC50 value of 98.3 IJs larva-1. Our results showed that S. abbasi PN-1 can be used as efficient biological control agents against H. armigera with further field studies.